2010
DOI: 10.1563/aaid-joi-d-09-00050
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Systemic Nicotine on Osseointegration of Titanium Implants in the Rat Femur

Abstract: The purpose of this study was to determine whether high levels of plasma nicotine, delivered via subcutaneously placed mini-osmotic pumps, had an effect on bone development and osseointegration of a titanium implant in rat femurs in both the short and long term. In this study, we hypothesized that systemic nicotine may not affect bone development, but may affect osseointegration in both the short and long term. Thirty rats were assigned to 4 groups. Group 1 (n = 10) was subdivided into 2 groups, which both rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Syversen et al[46]showed that female Sprague Dawley rats were exposed to nicotine vapour for 2 years and there was no difference in BMD between control rats and nicotine-exposed rats. Berley et al[47] and Yamano et al[48] indicated that systemic nicotine may have a significant adverse impact on bone wound healing and inhibit the bone matrix-related gene expressions required for wound healing. Brzóska et al [42,43] indicated that low exposure to cadmium (Cd) may affect the mineralization and biomechanical properties of growing bone, thus increasing the risk of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Syversen et al[46]showed that female Sprague Dawley rats were exposed to nicotine vapour for 2 years and there was no difference in BMD between control rats and nicotine-exposed rats. Berley et al[47] and Yamano et al[48] indicated that systemic nicotine may have a significant adverse impact on bone wound healing and inhibit the bone matrix-related gene expressions required for wound healing. Brzóska et al [42,43] indicated that low exposure to cadmium (Cd) may affect the mineralization and biomechanical properties of growing bone, thus increasing the risk of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be due to impair functions of MSCs or resident stem cells by nicotine. Berley et al reported decreased bone to implant contact after 4 weeks of implant placement in rats’ femur receiving subcutaneous nicotine (Berley et al , ). Likewise, Yamano et al reported a downregulation in the expression of bone matrix‐related genes around implants in rats receiving nicotine for 8 weeks (Yamano et al , ).…”
Section: E‐cigarette Aerosol Inhaled Nicotine and Periodontal Complmentioning
confidence: 99%
“…To evaluate our hypothesis, we used histomorphological and clinical parameters to evaluate the degree of bone formation and osseointegration. Micro-CT image analysis [36], removal torque measurements [37–43], and histomorphometric evaluation [21, 4347] are currently considered standard analyses in implant research. In the early healing stage, advancement of histomorphological changes and significantly increased functional analysis data were observed in the laser-implant group.…”
Section: Discussionmentioning
confidence: 99%